Predicting complications in pediatric Crohn's disease patients followed in CEDATA-GPGE registry - Klamt, Juliane; de Laffolie, Jan; Wirthgen, Elisa; Stricker, Sebastian; Däbritz, Jan; , the CEDATA-GPGE study group (Frontiers in Pediatrics, 2023)
Background. Complications of Crohn´s disease (CD) often impair patients’ quality of life. It is necessary to predict and prevent these complications (surgery, structuring [B2]/penetrating [B3] disease behavior, perianal disease, growth retardation and hospitalization). Our study investigated previously suggested and additional predictors by analyzing data of the CEDATA-GPGE registry. Methods. Pediatric patients (< 18 years) diagnosed with CD with follow up data in the registry were included in the study. Potential risk factors for the selected complications were evaluated by performing Kaplan-Meier survival curves and cox regression models. Results. For the complication surgery, the potential risk factors older age, B3 disease, severe perianal disease and initial therapy with corticosteroids at the time of diagnosis were identified. Older age, initial therapy with corticosteroids, low weight-for-age, anemia and emesis predict B2 disease. Low weight-for-age and severe perianal disease were risk factors for B3 disease. Low weight-for-age, growth retardation, older age, nutritional therapy, and extraintestinal manifestations (EIM) of the skin were identified as risk factors for growth retardation during the disease course. High disease activity and treatment with biologicals were predictors for hospitalization. As risk factors for perianal disease, the factors male sex, corticosteroids, B3 disease, a positive family history and EIM of liver and skin were identified. Conclusion. We confirmed previously suggested predictors of CD course and identified new ones in one of the largest registries of pediatric CD patients. This may help to better stratify patients´ according to their individual risk profile and choose appropriate treatment strategies.